Catch crops in the Argentinean Pampas: a synthesis-analysis on nutrient characteristics and their implications for a sustainable agriculture - Cafaro La Menza, Francisco; Carciochi, Walter Daniel (Frontiers in Agronomy, 2023)
Catch crops (CCs) are crops that grow between two cash crops, accumulating nutrients in their biomass and later releasing them through the decomposition of their residues. To our knowledge, no study has compared the nutrient-related traits of different CCs species. This comparison is essential for understanding the possible roles of CCs in agroecosystems and for optimizing adjustments of fertilizer rates. This study aims to: i) synthesize characteristics of the CCs, such as aboveground dry matter accumulation, nutrient [carbon (C), nitrogen (N), sulfur (S), and phosphorus (P)] concentration and accumulation, and C:nutrient ratios, ii) explore factors defining the mentioned characteristics, and iii) discuss their implications on the ecosystem services provided. By analyzing data from 52 studies, (98 site-years) in the Argentinean Pampas, we observed that grasses (excluding ryegrass) accumulated the greatest aboveground dry matter (6.08 ± 0.22 t ha -1 , mean ± SE) and C (2.60 ± 0.13 t ha -1 ), making them suitable for protecting the soil surface from erosion, suppressing weeds, and improving C balances. Conversely, vetch accumulated the highest nutrient content (118 ± 5.3, 15 ± 1.5, and 14 ± 1.2 kg ha -1 for N, S, and P, respectively) with the lowest C:nutrient ratio (means of 15:1, 152:1, and 147:1 for N, S, and P, respectively), making it a suitable choice for recycling nutrients and providing extra N. Mixtures presented intermediate characteristics between the monocultures, allowing a balanced provision of the mentioned ecosystem services. Furthermore, the results showed that dry matter accumulation affected the nutrient-related traits analyzed, and it was related to different factors, such as CCs sowing and termination dates or precipitation. The analysis highlights the importance of selecting CCs species based on the desired ecosystem service and provides valuable information for producers as well as for modeling C balances and nutrient cycling.